2016
DOI: 10.2308/iace-51431
|View full text |Cite
|
Sign up to set email alerts
|

Growing Up: How Audit Internships Affect Students' Commitment and Long-Term Intentions to Work in Public Accounting

Abstract: This study investigates factors that influence audit interns' commitment and long-term intentions to work in public accounting. We measure the organizational and professional commitment of 127 audit interns prior to the start of busy-season internships with public accounting firms and then again at the conclusion of the internship. We find that both organizational and professional commitment decline significantly as a result of the internship experience. We note that heavy workloads during the internship decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Experiential learning has helped to provide students with an opportunity to learn new things, outside of the classroom. Studies have shown that the role of supervision in internships cannot be understated (Hart et al, 2017;Schwartz-Bechet, 2014;Sweitzer & King, 2014). An important challenge that internship programs face is making sure that the intern's experience is educational (Stirling et al, 2017).…”
Section: Chapter Five: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiential learning has helped to provide students with an opportunity to learn new things, outside of the classroom. Studies have shown that the role of supervision in internships cannot be understated (Hart et al, 2017;Schwartz-Bechet, 2014;Sweitzer & King, 2014). An important challenge that internship programs face is making sure that the intern's experience is educational (Stirling et al, 2017).…”
Section: Chapter Five: Discussionmentioning
confidence: 99%
“…While the focus of experiential learning tends to be on job preparedness, there are many other positive outcomes to be gained from experiential learning, such as opportunities to network, opportunities to experience learning in a different context, and opportunities to grow as an individual (Kolb & Kolb, 2005). Hart, Kremin,and Pasewark (2017) examined an accounting internship program and found that commitment and long-term intentions to work in that particular field might be shaped by early employment experiences with regard to the size of workloads, the scope of work assignments, and the type working relations. While these results cannot be generalized to all fields or general internship programs, the results do point out that the role supervisors play in an internship is pivotal to the intern's success.…”
Section: Background Of the Studymentioning
confidence: 99%
See 2 more Smart Citations